"Telling a Story." On the Dramaturgy of Monophonic Jazz Solos - Frieler, Klaus; Pfleiderer, Martin; Abe, Jakob; Zaddach, Wolf-Georg (Empirical Musicology Review, 2016)
The metaphor of storytelling is widespread among jazz performers and jazz researchers. However, little is known about the precise meaning of this metaphor on an analytical level. The present paper attempts to shed light on the connected semantic field of the metaphor and relate it to its musical basis by investigating time courses of selected musical elements and features in monophonic jazz improvisations. Three explorative studies are carried out using transcriptions of 299 monophonic jazz solos from the Weimar Jazz Database. The first study inspects overall trends using fits of quadratic polynomials onto loudness and pitch curves. The second study does the same using selected features related to intensity, tension and variability over the course of phrases in the solos. The third study examines the distribution of the relative positions of various improvisational ideas in a subset of 116 solos. Results show that certain trends can be found, but not to a large extent. Significant trends most often display arch-shaped curves as expected from classical dramatic models. This is also in accordance with the fact that expressive improvisational ideas are more often found in the last part of a solo, while more relaxed ideas occur earlier. All in all, jazz improvisations show a wide range of variation and no single overarching dramatic model could be identified.